MODEL MANAJEMEN PEMBIAYAAN PENDIDIKAN BERBASIS MASYARAKAT DALAM RANGKA PENGEMBANGAN MADRASAH BERMUTU DI MTs AL HIKMATURROHMANIYAH SUKOREJO PASURUAN - Suadi (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: The article discusses the financing management model at MTs AlHikmaturrohmaniyahSukorejoPasuruan.Aqualitativeapproachwithdescriptiveanalysis wasusedinthisstudy.Thetechniqueofcollectingdataisbyinterview,observation,and documentation. The author uses the Miles and Hubberman models, data reduction, datadisplay, and verification / conclusion in analyzing data. The results of the study show: first,the financing management model at MTs Al-Hikmaturrohmaniyah Sukorejo Pasuruan hasbeen systematically following the management process, namely by implementing threeimportant paths in which includes planning income and expenditure budgets, overseeingeducation financing that departs from the planned needs of both madrasah and theprovisions of the local ministry of religion, the use of education funding is with certainconsiderations and priorities in previous planning, and supervision of education funding asa control and evaluation for future improvements. Second, the application of the financingmanagement model at MTs Al Hikmarurrohmaniyah Sukorejo Pasuruan is in accordancewith the principles of quality development in the financing sector with procedures forplanning, budgeting, supervision, and reporting. This is in accordance with the concept ofquality management that the development of quality is all forms of development activitiesthat must go through the process of planning, implementation, and reporting. Keywords: Financing Management, Quality, Budget